Exploring why portuguese companies expatriate, and portuguese expatriates accept international assignments - Martins, Dora (2015)
This study explores (1) the reasons that lead Portuguese companies to use expatriates and (2) the motivations that led the repatriates to accepting an international assignment. Semistructured interviews were carried out on 44 individuals (14 responsible for organizational management of the expatriates and 30 repatriates), in seven international companies based in Portugal, and analysis of the thematic content was conducted for data processing. Results suggest that the reasons that lead Portuguese companies to expatriating employees are connected to business needs and the control of international operations, while individual motivations are linked to personal and professional ambition, the will to serve the company and organizational pressure. We concluded that Portuguese companies, like most European companies, seem to develop a strategy of International Human Resources Management (IHRM) according to an ethnocentric approach, characteristic to companies in early stages of internationalization. Similarly, the main motivations of Portuguese repatriates are identical to those of other expatriates, though the will to serve the company seems to be more valued by Portuguese repatriates than by expatriates from other countries.